2020
DOI: 10.29333/ejeph/8324
|View full text |Cite
|
Sign up to set email alerts
|

Can Aerosols and Wastewater be Considered as Potential Transmissional Sources of COVID-19 to Humans?

Abstract: In view of the current situation regarding the COVID-19 disease, recently, published studies have proved the higher aerosol and surface stability of COVID-19. This virus, can survive long time on wastewater and aerosol. Therefore, its transmission via contaminated waste surfaces and airborne transmission through aerosols can occur besides close-distance contacts. This article discusses the potential presence of the COVID-19 pandemic on aerosol, wastewater and sewage sludge. This article highlights the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It has been proposed that the analysis of wastewater could be a powerful tool for COVID-19 surveillance. However, the documented presence of SARS-CoV-2 in wastewater raises the question regarding the potential transmission risk of this virus through wastewater, especially for those working with human waste and wastewater ( Foladori et al., 2020 ; Yang et al., 2020 ; Gormley et al., 2020 ; El Baz and Imziln, 2020 ; Gwenzi, 2021 ). Aerosols from wastewater treatment processes have the ability to carry infectious agents, including respiratory viruses, and therefore, might contribute to transmission of viral infections to the wastewater workers through aerosols/droplets produced in wastewater treatment plants (WWTP) ( Kitajima et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the analysis of wastewater could be a powerful tool for COVID-19 surveillance. However, the documented presence of SARS-CoV-2 in wastewater raises the question regarding the potential transmission risk of this virus through wastewater, especially for those working with human waste and wastewater ( Foladori et al., 2020 ; Yang et al., 2020 ; Gormley et al., 2020 ; El Baz and Imziln, 2020 ; Gwenzi, 2021 ). Aerosols from wastewater treatment processes have the ability to carry infectious agents, including respiratory viruses, and therefore, might contribute to transmission of viral infections to the wastewater workers through aerosols/droplets produced in wastewater treatment plants (WWTP) ( Kitajima et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Though till now there is no report on SARS-CoV-2 in aerosols from WTPs, studies by Fears et al. (2020 ) shows its infectivity in aerosols for up to 16 h, and studies by El Baz and Imziln (2020 ) indicates its potential risk if found in wastewater aerosol.…”
Section: Concern Is Already Raised: “Presence Is Confirmed In Sewage mentioning
confidence: 99%
“…Researchers studied the production of microbial aerosols and their health impacts on plant operators during WWTP processes [38,189,190]. Recent publications have proved that COVID-19 is highly stable in aerosols (viruses live for several hours) and on surfaces (viruses live for several days) [1].…”
Section: Analysis For Each Uwc Component 41 Wastewater Treatment Plants (Wwtps)mentioning
confidence: 99%